The Digital Leap: How Technology Shapes Employee Perceptions of Professionalism and Productivity in Project Supervision - Putri, Faradilla Sukmawati Permata; Manafe, Leonard Adrie; Emmywati, Emmywati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study investigates how employees at CV. Cakrawala Design, a project planning and supervision agency, assess their professionalism and productivity amid the wave of digitalisation. A qualitative approach with a case study design was chosen to ensure that the voices of those on the ground are heard directly. Five informants from various job levels were interviewed without restrictions on their fields to capture hidden nuances. Synchronous observations were then conducted to compare verbal acknowledgments with actual behaviour. Initial findings show that cloud-based software and team chat rooms can cut coordination time by almost half. On the other hand, the flow of tutorials, notifications, and application updates pushed some workers to the brink of overwhelm. Therefore, this study underscores the importance of ongoing training sessions and social dialogue spaces to ensure that technology truly supports rather than dampens morale. Final recommendations urge Cakrawala Design management to embrace daily employee feedback when crafting future digital initiatives.